2022
DOI: 10.1093/geroni/igac045
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Built Environment on the Quality of Life for Residents in Long-Term Care Facilities in Asia: A Scoping Review

Abstract: Background and Objectives The quality of the built environmental features in a long-term care (LTC) home significantly influences residents’ functioning (e.g., wayfinding, self-care, and social interaction) and well-being. There is limited research on the characteristics of the built environment of LTC and its influence on residents’ quality of life in countries in Asia-Pacific region (e.g., East Asia, South Asia). The older adult population in this region is expected to increase significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Existing evidence suggests that the built environment plays a significant role in the prevalence of CKD ( McClellan et al, 2012 ). As an important health-related component of the built environment, green space has attracted considerable attention in the literature, as it can be easily addressed through urban planning policy ( Chaudhury & Xu, 2022 ; Liang et al, 2022 ; Liu et al, 2023 ; Lu et al, 2022 ; Park et al, 2021 ; Shen, 2022 ). For example, Liang et al (2022) found that residential greenness was associated with a decreased prevalence of CKD in China.…”
mentioning
confidence: 99%
“…Existing evidence suggests that the built environment plays a significant role in the prevalence of CKD ( McClellan et al, 2012 ). As an important health-related component of the built environment, green space has attracted considerable attention in the literature, as it can be easily addressed through urban planning policy ( Chaudhury & Xu, 2022 ; Liang et al, 2022 ; Liu et al, 2023 ; Lu et al, 2022 ; Park et al, 2021 ; Shen, 2022 ). For example, Liang et al (2022) found that residential greenness was associated with a decreased prevalence of CKD in China.…”
mentioning
confidence: 99%